2014
DOI: 10.1007/s10157-014-1067-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum and urinary soluble urokinase receptor (suPAR) in primary nephrotic syndrome and MPO-ANCA-associated glomerulonephritis in Japanese

Abstract: S- and u-suPAR after therapy may serve as clinical markers to judge the treatment response of untreated NS and differentiate MCNS from FSGS, but not in pretreatment patients. S-, but not u-suPAR may predict the severity of and crescent formation in ANCA-GN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Similar to Fujimoto et al's results [25], we also detected that the suPAR levels positively correlated with CRP and inversely correlated with eGFR levels. In addition, we demonstrated that there is an association between the concentration of suPAR with other clinical parameters in AAV, including BVAS, PCT, and C3, further revealing a close relationship between suPAR levels and disease activity.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to Fujimoto et al's results [25], we also detected that the suPAR levels positively correlated with CRP and inversely correlated with eGFR levels. In addition, we demonstrated that there is an association between the concentration of suPAR with other clinical parameters in AAV, including BVAS, PCT, and C3, further revealing a close relationship between suPAR levels and disease activity.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study indicated independent associations between increased plasma suPAR levels and incident chronic kidney diseases (CKD) [24]. Fujimoto et al [25] reported significant higher suPAR levels in 13 patients with MPO-ANCAassociated glomerulonephritis (ANCA-GN) and indicated that these levels might be a useful marker to assess clinical severity of ANCA-GN. Meanwhile, the role of suPAR in AAV is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, 364 studies were initially included, among which 306 studies were excluded after reading the title and abstract. After reading the full text, another 29 studies were excluded; therefore, 29 studies were finally included 9–11 21–46. A flow chart of the study selection process is presented in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the patients with hypocomplementemia had high urine protein levels (2.24 g/gCr). Fujimoto et al [23] reported that 13 patients with MPO-ANCA-associated glomerulonephritis had 1.2 (0.6–2.0) g/gCr (median interquartile range]) of urine protein. This result may support our hypothesis that immune complexes have an important role in the pathogenesis of AAV with hypocomplementemia.…”
Section: Discussionmentioning
confidence: 99%